Press Law as Social Engineering in Improving the Literacy of Sailor Tribe Communities in Maumere Bay Who are Vulnerable to Hoax News and Hate Speech - Da Cunha, Theresia; Yonas K. G. D Gobang; Yosefina Daku (Journal of Law, Politic and Humanities, 2025)
This research raises the urgency of the importance of press law as a social engineering tool in improving the literacy of the Sailor Tribe community in Maumere Bay, Flores, NTT, which is vulnerable to hoax news and hate speech. The complex social context and problems increasingly troubling the community require a holistic approach involving legal, social, and educational aspects. The main objectives of this research were to identify the role of press law in improving the literacy of the Sailor Tribe community in Maumere Bay and reducing the negative impact of the spread of hoax news and hate speech. The research method used was a combination of normative and empirical including descriptive analysis, qualitative, interviews, media content analysis, and educational program development. Through this approach, an effective strategy was found to utilize press law as an instrument of positive social engineering. This research had not only academic relevance but also important practical implications to increase public understanding of correct and responsible information and reduce the negative impact of spreading hoax news and hate speech.